An attack on undeniable partially blind signatures - Han, Song; Chang, Elizabeth; Wang, J. (Springer-Verlag, 2005)
Blind signatures allow a user to get a signature on any message without revealing the content of the message to the signer. Partially blind signatures allow the signer to explicitly include common information in the blind signature under some agreement with the user. Undeniable signatures can only be verified with the help of the signer. However, if a signature is only verifiable with the aid of the signer, a dishonest signer may disavow a genuine document. Undeniable signatures solve this problem by adding a new component called the disavowal protocol in addition to the normal components of signature and verification. Disavowal protocol can prevent a dishonest signer from disavowing a valid signature. The convertible undeniable signatures allow the signer to convert given signatures into universally verifiable signatures. To combine all the above characteristics, Huang et al. proposed a convertible undeniable partially blind signature scheme at IEEE AINA 2005. They extended the concept of partially blind signature to the convertible undeniable partially blind signature, in which only the signer can verify given signatures on messages, and confirm/disavow the validity/invalidity of given signatures, and convert them into universally verifiable signatures. However, their scheme is not secure. In this paper, we present an attack on the convertible undeniable partially blind signature scheme.